Probing on Growth and Characterizations of SnFe2O4 Epitaxial Thin Films on MgAl2O4 Substrate - Gupta, Ram K.; Candler, J.; Kumar, D.; Gupta, Bipin K.; Kahol, Pawan K. (Frontiers in Materials, 2014)
Epitaxial tin ferrite (SnFe2O4) thin films were grown using KrF excimer (248 nm) pulsed laser deposition technique under different growth conditions. Highly epitaxial thin films were obtained at growth temperature of 650 ˚C. The quality and epitaxial nature of the films were examined by X-ray diffraction technique. Furthermore, the phi scans of the film and substrate exhibit four folds symmetry which indicates a cube-on-cube epitaxial growth of the film on MgAl2O4 substrate. Moreover, the magnetic force microscopy measurement shows domains with cluster-like structure which is associated with ferromagnetic phase at room temperature. The coercive field and remnant magnetization of the films decrease with increase in temperature. These high quality ingenious magnetic films could be potentially used in data storage devices.